ANALYZING VIRTUAL CHAT EFFECTIVENESS: A COMPARATIVE STUDY OF LIBRARY PROFESSIONALS AND UNDERGRADUATE EMPLOYEES - Benjamin , Thomas Mitchell (Current Journal of Library and Information Sciences (CJLIS), 2023)
Over the past few decades, library patrons have been engaging with libraries through virtual means, with some services dating back to the late 1980s. As technology has continued to advance, the utilization and monitoring of virtual reference chat services have become more streamlined, offering increased convenience for both library staff and patrons. These technological enhancements have also enabled libraries to gather and analyze quantitative statistics and qualitative data from these chat interactions. Moreover, the staffing models for chat services have evolved, with a transition from relying solely on professional librarians as chat respondents to including paraprofessional staff, graduate students, and undergraduate students. In this context, this paper seeks to address a critical question regarding the effectiveness of different employee types (non-student and student) in responding to virtual reference chats. For the purposes of this study, "non-student" employees encompass professional librarians and paraprofessional library staff, while "students" refer to undergraduate student employees. Graduate students are not considered in this classification, as they are typically not part of the reference desk staffing. While some assessment has been conducted regarding the ability of students to handle virtual reference chats, there exists a clear need for further research that compares the efficacy of different employee types. This research aims to ensure the delivery of high-quality service to library patrons engaging with virtual reference chat services.